Efektivitas Pengaturan Sanksi Hukum terhadap Cyberstalking dalam Undang-Undang Informasi dan Transaksi Elektronik - Rahmat Pajri; Julius Anggara; Rahmad Hidayat; Yovi Arianda (Consensus : Jurnal Ilmu Hukum, 2025)
The internet does bring many benefits, but on the other hand it also creates new threats, one of which is cyberstalking harassment or intimidation carried out through cyberspace. This research discusses how to prevent and take action against cyberstalking perpetrators by referring to the 2016 ITE Law. Prevention efforts can start from simple things, such as maintaining digital security, saving evidence of disturbing messages, to reporting them to the authorities or social media admins. On the other hand, the government also needs to strengthen regulations so that law enforcement is clearer, while the public is required to be increasingly aware of the importance of digital legal literacy. In the end, protection from cyberstalking can only be effective if there is cooperation between individuals, authorities and the state.